KARAKTERISTIK DAN ANALISIS KEKERABATAN RAGAM KELAPA (Cocos nucifera L.) DI KABUPATEN MANGGARAI BARAT BERDASARKAN KARAKTER MORFOLOGI DAN ANATOMI - Gunawati, Leonarda; Kriwiyanti, Eniek; Joni, Martin (SIMBIOSIS, 2018)
Research on the characteristic and analysisof coconut kernels ( Cocos nucifera L.) in west Manggarai district has been done to determine the variety, kinship and coconut plant benefits( Cocos nucifera L.).Cocos nucifera L. Exploration was conduction in west Manggarai – Flores regency and preparatory preparationwasdone in Plant Structure Development Laboratory, conducted from February to July 2016. Exploration was done by observation and to make the description according to Book Center for Plant Variety Protection (PPVT) 2007. ( Cocos nucifera L.) morphological and anatomical observation results descriptive for identification. The discarded qualitative and quantitative dara are presented in OTU table (OperationTaksonomy Unit) to create a dendogram withMinitab program vis 14. Research results the were eight varietas of coconut plants ( Cocos nucifera L.) Nio Kuse, Nio Taak Tua, Nio Taak Ngoel, Nio Sangon, Nio Ndereng, Nio Kuning and Nio Lolo. Based on morphological and anatomical characteristics and at similarity level (32.1%) eight coconuts in separate West Manggarai into 8 groups All parts of the coconut plant have economic benefits especially old coconut fruit has a thick fruit flesh (1.7 cm) and Nio Sangon has the (2.6kg weight Keywords : k inship, e xploration, q uantitative, q ualitative, i dentification